2023
DOI: 10.3399/bjgpo.2022.0173
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determinants of GPs’ work hours in the UK: a quantitative study

Abstract: BackgroundInformation on the hours of work of UK doctors is limited, and what exists relies on self-designed questionnaires in England.AimTo understand trends in the annual stock of physicians’ hours and their main determinants.Design and settingData were collected from the Quarterly Labour Force Survey (QLFS) between 1998 and 2020 under the End User License (EUL).MethodDescriptive and linear regression models of labour supply for doctors (pooled), GPs, and hospital doctors.ResultsBetween 1998 and 2020, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
0
0
Order By: Relevance
“…Comparable trends exist in the United States, 24 where average weekly physician hours dropped 7.6% between 2001 and 2021, predominantly because of the decline in hours worked by male physicians, 6 and in the United Kingdom, where average hours for general practitioners and hospital-based physicians dropped by 25% and 21%, respectively, between 1998 and 2020. 25 Similar observations in jurisdictions with different health care systems support our suggestion that these trends reflect a cultural shift, primarily among male physicians, toward more balanced home and work lives.…”
Section: Discussionsupporting
confidence: 77%
“…Comparable trends exist in the United States, 24 where average weekly physician hours dropped 7.6% between 2001 and 2021, predominantly because of the decline in hours worked by male physicians, 6 and in the United Kingdom, where average hours for general practitioners and hospital-based physicians dropped by 25% and 21%, respectively, between 1998 and 2020. 25 Similar observations in jurisdictions with different health care systems support our suggestion that these trends reflect a cultural shift, primarily among male physicians, toward more balanced home and work lives.…”
Section: Discussionsupporting
confidence: 77%
“…A recent cross-sectional study among 3236 GPs from China found that 58.56% of the participants suffered from high levels of occupational stress with overtime being directly linked to the development of occupational stress [57]. Besides causing chronic stress, overtime also leads to an increased intention of GPs to work part-time according to a quantitative study from the UK: in the time period between 1998 and 2020, the working hours dropped by 25.37% [58]. Another cross-sectional survey with a sample of 320 German GPs identified out-of-hours care as an important stressor in everyday practice and a reason for lower job satisfaction.…”
Section: Discussionmentioning
confidence: 99%